REAKSI PASAR ATAS PENGUMUMAN BUYBACK SAHAM PADA SAAT PANDEMI COVID-19 DI BURSA EFEK INDONESIA - Purwitha, Ida Bagus Surya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022, 2022)
This study aims to determine whether the market reaction to the announcement of share buybacks has a positive effect during the covid-19 pandemic. The population of this research is 68 companies. The sampling technique used purposive sampling method, the samples obtained were 60 companies. The proxy in measuring market reaction uses cumulative abnormal return (CAR). The data analysis technique used is descriptive analysis, one sample t-test. The market reacted negatively at the time of the announcement of the stock buyback, before the event and after the event. This situation is different from normal conditions if investors receive good information then the market will react positively. The Covid-19 outbreak has made market conditions uncertain, resulting in a decline in IHSG. Information on share buyback announcements and capital information issued by companies to conduct share buybacks is good information or positive information, but the information has little effect compared to the impact of covid-19 and has not been able to give confidence to investors.